Phenotypic diversity and molecular characterization of male sterility based on cytotype and Ms locus variation in Indian onion germplasm - S. Santhiya; Nirmal Kumar Hedau; Anamika Thakur; Anu Singh; Rahul Dev; Lakshmi Kant (Molecular Biology Reports, 2026)

Assessment and prediction of snow cover dynamics over Siachen using advanced statistics and Hybrid Seasonal-Trend Fourier Regression model - Aditya Kumar Thakur; Harshita Tiwari; Rahul Dev Garg; Kamal Jain (Cold Regions Science and Technology, 2026)

Enhanced precipitation estimation in a Himalayan river basin through the fusion of multi-source datasets using various machine learning techniques - Harshita Tiwari; Aditya Kumar Thakur; Rahul Dev Garg (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

UAV-derived bathymetry of a gravel-bed river mesohabitat mapping and hydromorphological assessment - Rohit Sharma; Miloš Rusnák; Zulfequar Ahmad; Rahul Dev Garg; Soheyl Moradi; Matej Vojtek (Geomorphology, 2026)

Machine Learning Based Location Estimation for Analysing GPS Accuracy - Pankaj P. Tasgaonkar; Rahul Dev Garg; Pradeep Kumar Garg; Poonam Bhosale (Journal of the Indian Society of Remote Sensing, 2026)

Surface functionalization and interfacial engineering of lignocellulosic fibers for high-performance biopolymer composites - Mohd Zulhafni Mad Rahis; Rahul Dev Bairwan; H.P.S. Abdul Khalil; Shahdan Abas; Nor Saidi Mohamed Nasir; Rohayati Mohd Isa (Bioresource Technology Reports, 2026)

Multidimensional InSAR for accurate glacier velocity reconstruction: overcoming LOS underestimation in complex terrain - Shubham Bhattacharjee; Rahul Dev Garg; Arvind Chandra Pandey (Advances in Space Research, 2026)

Insights on urban expansion control around the urban waterbodies of developed and developing countries using remote sensing - Arnab Mondal; Rahul Dev Garg; Kunwar K Singh (Journal of Earth System Science, 2026)

Bio-based nanocomposite films from Kappaphycus alvarezii for packaging applications - Rahul Dev Bairwan; Nur Thohiroh Md Bukhari; Mohamad Haafiz Mohamad Kassim; Mohd Nurazzi Norizan; C.K. Abdullah; Nurul Fazita Mohammad Rawi (Biomass and Bioenergy, 2026)

Structural and interfacial characterization of seaweed biocomposite films reinforced with rice husk-derived silica nanoparticles - Nur Thohiroh Md Bukhari; Rahul Dev Bairwan; Mohamad Haafiz Mohamad Kassim; Mohd Nurazzi Norizan; C.K. Abdullah; Nurul Fazita Mohammad Rawi (Bioresource Technology Reports, 2026)

Agro-morphological and biochemical characterization of Phaseolus vulgaris landraces from the Indian Western Himalayas - Pooja Oli; Shailaja Punetha; Rahul Dev (Food and Humanity, 2026)

Exploring Kolmogorov–Arnold networks for hyperspectral crop classification – an evaluative study - Shruti Gupta; Ashish Kumar; Rahul Dev Garg; Neeraj Jain (Advances in Space Research, 2026)

Fate and state of small and medium-sized glaciers of Himachal Pradesh, India: a geospatial-based perspective - Shubham Bhattacharjee; Rahul Dev Garg; Arvind Chandra Pandey (Journal of Earth System Science, 2026)

Comprehensive Assessment of Ground Deformation Dynamics and Displacement Patterns in Jeenagora Opencast Coal Mining Region of Jharia Coalfield Using PS-InSAR and Advanced Statistical Analysis - Aditya Kumar Thakur; Rahul Dev Garg; Kamal Jain (Natural Resources Research, 2026)

Hybrid Ensemble Framework for Enhanced Crop Classification Using Hyperspectral Remote Sensing - Ashish Kumar; Rahul Dev Garg (Journal of the Indian Society of Remote Sensing, 2026)

Prediction of Tropospheric Nitrogen Dioxide in Kolkata Using Sentinel-5p and Sentinel-2 Multispectral Data and Machine Learning Algorithm - Aman Srivastava; Aditya Kumar Thakur; Rahul Dev Garg; Pradeep Kumar Garg (Journal of the Indian Society of Remote Sensing, 2026)

In silico retrieval of sulfiredoxin from Setaria italica, Panicum miliaceum, and Eleusine coracana: Sequence characterization, structural modeling, and protein–protein interaction analysis - Rahul Thakur; Arvind Gupta; Kanchan Rauthan; Deepti Dixit; Arzoo Choudhary; Ashutosh Kumar Pandey; Atul Krishna Dev; Saurabh Yadav (Plant Gene, 2026)

A Comprehensive Assessment of Spatiotemporal Dynamics of Urban NO2 using Sentinel-5P with Evaluation of the Predictive Capability of Sentinel-2 for Pollution Estimation - Aman Srivastava; Aditya Kumar Thakur; Rahul Dev Garg; Pradeep Kumar Garg (Water, Air, & Soil Pollution, 2026)

Sustainable seaweed-based biopolymer films reinforced with rice husk-derived silica nanoparticles for eco-friendly packaging applications - Nur Thohiroh Md Bukhari; Rahul Dev Bairwan; Mohamad Haafiz Mohamad Kassim; CK Abdullah; Norfarhah Binti Abdul Razak; Mohd Shahrieel Mohd Aras; H.P.S. Abdul Khalil; Nurul Fazita Mohammad Rawi (Journal of Environmental Chemical Engineering, 2026)

From dimensions to decisions: A Siamese Neural Network for comprehensive analysis of intrinsic dimensionality estimation and dimensionality reduction in hyperspectral imaging - Ashish Kumar; Rahul Dev Garg (Journal of Earth System Science, 2026)

Performance and Emission Evaluation of a CRDI Diesel Engine Fueled with Algae Biodiesel and Hydrogen Enrichment - Debarup Borah; Rahul Dev Misra (Emission Control Science and Technology, 2026)

A comprehensive assessment of vegetation and water resource dynamics in Bihar using Sentinel-2 derived NDVI and NDWI indices - Aditya Kumar Thakur; Aman Srivastava; Rahul Dev Garg; Kamal Jain (Journal of Earth System Science, 2026)

How spatiotemporal urban expansion shapes heat trends in coastal megacities: Developed vs. developing nations - Dyutisree Halder; Harshit; Rahul Dev Garg (Urban Climate, 2025)

Harnessing agro-food organic residues for biodegradable materials: Toward circular and sustainable solutions - Budi Susetyo; H.P.S. Abdul Khalil; Rahul Dev Bairwan; Rimun Wibowo; Mohamad Sam'un; Nurul Fazita Mohammad Rawi (Bioresource Technology Reports, 2025)

Diversity and Functional Characterization of Endophytes in Two Contrasting Cultivars of Ocimum sanctum: Insights from Culture-Based and Metagenomic Approaches - Rahul Kumar Gupta; Shiwangi Singh; C S Chanotiya; Kapil Dev; Prabodh Kumar Trivedi; Akanksha Singh (Journal of Plant Growth Regulation, 2025)

Effects of Mulching On Soil, Growth, and Biochemical Traits of Strawberry (Fragaria × ananassa) Under Protected Cultivation - Shailaja Punetha; Pooja Oli; Nidhi Joshi; Supriya Gupta; Prabhat Kumar; Manpreet Singh Preet; Vineet Kaswan; Rahul Dev; A. K. Goswami; Anjali Jingar; Daya Shankar Mishra; Prakashbhai Ravat; et al. (Applied Fruit Science, 2025)

Development of crash modification factor for lane and shoulder width: a matched case-referent approach - Ankit Choudhary; Rahul Dev Garg; Sukhvir Singh Jain (Innovative Infrastructure Solutions, 2025)

Spatiotemporal Variation in Sea Ice Concentration Using Sentinel-1 Satellite Data and Radar Polarimetry: a Case Study of northern Greenland - Shubham Bhattacharjee; Rahul Dev Garg (Remote Sensing in Earth Systems Sciences, 2025)

Unravelling the detection of Carrington storm of 1859 from the historical magnetic declination observations of Trivandrum observatory - R. Jayakrishnan; C.K. Fazil; L. Rahul Dev; A. Ajesh (Advances in Space Research, 2025)

Spatiotemporal analysis of NO2 trends over major air pollution hotspots in India using Sentinel-5P - Aman Srivastava; Aditya Kumar Thakur; Rahul Dev Garg; Pradeep Kumar Garg (Journal of Earth System Science, 2025)

Comprehensive analysis of line-of-sight displacement and periodicity in ascending and descending pass time-series ground deformation in the mining-affected East Jharia Coalfield - Aditya Kumar Thakur; Rahul Dev Garg; Kamal Jain (Journal of Earth System Science, 2025)

An Overview of the Design and Realized Performance of Ocean Colour Monitor (OCM-3) Payload On-Board the Oceansat-3 (EOS-06) Mission - Vishnukumar D. Patel; Manoj Kumar; Pradeep Soni; Rahul Dev; Dheeraj Adlakha; Moumita Dutta; Dhrupesh S. Shah; Manoj P. Detroja; Harish Seth; Ashok Kumar; Jimit Gadhia; P. Nandha Kumar; et al. (Journal of the Indian Society of Remote Sensing, 2025)

Comparative study of lignin from patchouli waste fibers and spent coffee grounds as biofillers in poly(3-hydroxybutyrate-co-3-hydroxyvalerate)-based biodegradable packaging materials - Syaifullah Muhammad; Rahul Dev Bairwan; H.P.S. Abdul Khalil; Marwan Marwan; Mardiana Idayu Ahmad; C.K. Abdullah (Bioresource Technology Reports, 2025)

Land subsidence dynamics and its structural impact assessment over East Jharia, Jharkhand, India - Aditya Kumar Thakur; Rahul Dev Garg; Kamal Jain (Journal of Earth System Science, 2025)

Global urban flood dynamics and future vulnerability assessment: a comprehensive study of trends, predictions, and mitigation - Arnab Mondal; Rahul Dev Garg (Natural Hazards, 2025)

Spatio–temporal analysis of traffic crash hotspots- an application of GIS-based technique in road safety - Ankit Choudhary; Vishal Mishra; Rahul Dev Garg; S. S. Jain (Applied Geomatics, 2025)

Assessing the role of sustainable water bodies in urban drainage systems to mitigate urban flooding: A case study of Gurgaon, Haryana, India - Arnab Mondal; Rahul Dev Garg (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Sustainable cellulose extraction: unlocking the potential of tropical fruit peels for advanced materials - Azfaralariff Ahmad; H. P. S. Abdul Khalil; Rahul Dev Bairwan; Mardiana Idayu Ahmad; Amirul Al-Ashraf Abdullah; Che Ku Abdullah; Esam Bashir Yahya; Mohamad Shazeli Che Zain; Shazlina Abd Hamid (Clean Technologies and Environmental Policy, 2025)

Recent Advancements in Metabolomics: Applications and Insights into Functional Beverages - Rahul Dev; Manoj S. Aroor; Mahesh Gupta (Current Food Science and Technology Reports, 2025)

An assessment of the spatiotemporal dynamics and seasonal trends in NO₂ concentrations across India using advanced statistical analysis - Aman Srivastava; Aditya Kumar Thakur; Rahul Dev Garg (Remote Sensing Applications: Society and Environment, 2025)

An assessment of different line-of-sight and ground velocity distributions for a comprehensive understanding of ground deformation patterns in East Jharia coalfield - Aditya Kumar Thakur; Rahul Dev Garg; Kamal Jain (Remote Sensing Applications: Society and Environment, 2025)

Multi-environment evaluation of Clary sage (Salvia sclarea L.) selections for yield and essential oil traits under Western Himalayan conditions - Ajay Kumar; Romika Thakur; Rahul Dev Gautam; Ramesh Chauhan; Dinesh Kumar; Ashok Kumar; Satbeer Singh; Sanatsujat Singh (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

GIS-Based optimum path analysis for tourist places in Haridwar City - Pankaj P. Tasgaonkar; Rahul Dev Garg; Pradeep Kumar Garg (Applied Geomatics, 2024)

Synergistic Bioactivity of Aegiceras corniculatum (L.) Blanco and Its Endophytic Fungus Aspergillus: Antioxidant, Antimicrobial, and Cytotoxic Effects - Sharika Noshin; Rahul Dev Bairagi; Sadia Airin; Dipa Debnath; Md. Sohanur Rahaman; Amit Kumar Acharzo; Most. Nazmin Aktar; Mohammed Bourhia; Ahmad Mohammad Salamatullah; Md. Amirul Islam (Cell Biochemistry and Biophysics, 2024)

Discerning the dynamics of urbanization-climate change-flood risk nexus in densely populated urban mega cities: An appraisal of efficient flood management through spatiotemporal and geostatistical rainfall analysis and hydrodynamic modeling - Rahul Deopa; Dev Anand Thakur; Satish Kumar; Mohit Prakash Mohanty; Punyo Asha (Science of The Total Environment, 2024)

Inferring glacier mass balance from Sentinel-1 derived ice thickness changes using geoinformatics: A case study of Gangotri glacier, Uttarakhand, India - Shubham Bhattacharjee; Rahul Dev Garg (Remote Sensing Applications: Society and Environment, 2024)

First comprehensive evaluation of genetic variability for bacterial blight resistance in wild Punica granatum L. populations from the North-Western Himalayas - Rahul Sharma; Som Dev Sharma; Vikas Kumar Sharma; Monica Sharma; Dinesh Kumar; Rajat Sharma; Yashasvi Thakur; Shireen Khatri (Physiological and Molecular Plant Pathology, 2024)

Natural wax recovery from Musa acuminata biomass using organic solvents - Dhananjay Singh; Mukul Sengar; Tanya Gupta; Sunita Singh; Deepak Singh; Vinay Mishra; Rahul Dev; Balendu Shekher Giri (Chemosphere, 2024)

Spatiotemporal variability in surface velocity of large tributary-bearing glaciers of the Indian Himalayas inferred from SAR polarimetry - Shubham Bhattacharjee; Rahul Dev Garg (Hydrological Sciences Journal, 2024)

Development of a continuous electrochemical reactor incorporated with waste-derived activated carbon electrode for the effective removal of hexavalent chromium from industrial effluent - Aravind Sreekumaran Nair Prasannakumari; Gokul Dev Pallithazhath Madhu; Rahul Krishna Bhuvanendran; Soundararajan Bhuvaneshwari (Environmental Science and Pollution Research, 2024)

Enhancement of fuel-grade oil yields from thermal pyrolysis of polyethylene and polystyrene through reflux condenser assisted autoclave reactor - Amarendra Deka; Rahul Dev Misra (Clean Technologies and Environmental Policy, 2024)

Genetic variability, characters association and principal component study for morphological and fodder quality of Opuntia and Nopalea sp. in India - Rahul Dev; Shamsudheen Mangalassery; Devi Dayal; Mounir Louhaichi; Sawsan Hassan (Genetic Resources and Crop Evolution, 2024)
A morphological and quality analysis of 64 global core collections of cactus genotypes was conducted using 30 growth and fodder quality traits. Results indicated a high coefficient of variation for primary cladode perimeter (91.0%), root fresh weight (50.8%), and number of cladodes per plant (47.7%). The length, width, and thickness of the primary cladode ranged between 14.4 to 53.9 cm, 5.0 to 13.7 cm, and 1.5 to 4.3 cm, respectively. Principal component analysis showed a 77.6% variation in the first 10 major components with an eigenvalue > 1.0. The first and second principal components explained 18.5% and 14.8% of the total variation, respectively. The fresh weight of the shoot was positively correlated with the dry weight of the shoot (0.72), dry weight of the root (0.48), root length (0.38), and fresh weight of primary cladodes (0.29). The dendrogram obtained using a Ward analysis confirmed the results of the PCA analysis. The cactus pear accessions were grouped into four major clusters with a further four sub-clusters, containing 6, 26, 17 and 15 genotypes, respectively. Genotypes, CAZRI-Kukma, Clone 1308, Jalpa, Mexico Unknown, Trunzara Bianca Bronte, Copena F1, CAZRI Botanical Garden, Piantra-25 and IPA-90-18 are positioned at a wider angle and are more diverse and useful genotypes for use as parent populations for developing new genotypes in future breeding programs.

Elucidating the physical, chemical, functional and antioxidant properties of protein-rich quinoa (Chenopodium quinoa) crisp - Rahul Dev; Mahesh Gupta (Food and Humanity, 2024)

Enhancement micro filler spent coffee grounds in catalyst - chemically modified bast fibers reinforced biodegradable materials - M. Marwan; Eti Indarti; Rahul Dev Bairwan; H.P.S. Abdul Khalil; C.K. Abdullah; Azfaralariff Ahmad (Bioresource Technology Reports, 2024)

Estimation of sea ice drift and concentration during melt season using C-band dual-polarimetric Sentinel-1 data - Shubham Bhattacharjee; Rahul Dev Garg (Remote Sensing Applications: Society and Environment, 2024)

Examining effect of super-resolution on AVIRIS-NG data: A precursor to generation of large-scale urban material and natural cover maps - Kavach Mishra; Asfa Siddiqui; Vinay Kumar; Kamal Pandey; Rahul Dev Garg (Advances in Space Research, 2024)

Microsatellite markers’ based molecular divergence among the breeding lines of aromatic marigold (Tagetes minuta L.) - Ajay Kumar; Hari Sharan; Diksha Dhiman; Rahul Dev Gautam; Ramesh Chauhan; Ashok Kumar; Satbeer Singh; Sanatsujat Singh (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Sustainability issues of solar desalination hybrid systems integrated with heat exchangers for the production of drinking water: A review - Dhananjay Singh; Deepak Singh; Vinay Mishra; Jyoti Kushwaha; Rahul Dev; Suresh Kumar Patel; Ravi Shankar; Balendu Shekher Giri (Desalination, 2023)

Experimental investigation and performance analysis of box-type standard solar cooker with an inclined cover (BTSCIC) - Bhupendra Koshti; Rahul Dev; Ajaya Bharti; Audhesh Narayan (Environmental Science and Pollution Research, 2023)

Delineation of agricultural fields in arid regions from Worldview-2 datasets based on image textural properties - Abhishek Adhikari; Rahul Dev Garg; Sunil Kumar Pundir; Anupam Singhal (Environmental Monitoring and Assessment, 2023)

Potential of DESIS and PRISMA hyperspectral remote sensing data in rock classification and mineral identification:a case study for Banswara in Rajasthan, India - Prateek Tripathi; Rahul Dev Garg (Environmental Monitoring and Assessment, 2023)

Assessing variations in land cover-land use and surface temperature dynamics for Dehradun, India, using multi-time and multi-sensor landsat data - Kavach Mishra; Rahul Dev Garg (Environmental Monitoring and Assessment, 2023)

Notes on Grewia tenax (Forssk.) Fiori: an underutilized multipurpose shrub of hot arid region of western Rajasthan - Anil Patidar; K. Venkatesan; J. P. Singh; Rahul Dev; Pavan Kumar Malav; Mahesh Kumar; S. C. Meena; Archana Sanyal; Mavji Patidar (Genetic Resources and Crop Evolution, 2022)

Coastal Protection Using Integration of Mangroves with Floating Barges: An Innovative Concept - Rahul Dev Raju; Madasamy Arockiasamy (Journal of Marine Science and Engineering, 2022)
Mangroves and moored barges are used individually for coastal protection and beach restoration. This conceptual paper discusses about the integration of mangroves with moored floating barges for coastal protection. The concept involves towing of a barge to a particular location, mooring it to the seafloor and planting mangroves along the shore or beach. The barges will be unmoored and towed away once the mangroves attain certain growth and are well rooted in the soil. Mangroves can protect the beach from incoming waves using their roots and branches. The incoming waves can be reduced by 50% to 99% using mangroves of 500 m width. Mangroves have a life span of 20–100 years, and they do not need any yearly maintenance as do any other conventional coastal protection measures. Mangroves are considered as soft coastal protection structures and are environmentally friendly. Mangroves will also improve the aesthetic appearance of the beach. This paper discusses about some of the research methodologies for the development of the barge-assisted mangroves coastal protection method. The dimensions of the barge, gap width between the moored barges and the environmental condition at the location determines the performance of the barge-assisted mangroves coastal protection method. The gap width between the barges, draft of the barge and breadth of the barge influence the resonant frequency of the fluid between the barges. The shielding effect of the floating barges can be used for other applications, such as berthing of ships and growing living shorelines using oysters, rocks, sand, plants, coir, etc. for coastal protection.

Calcareous peloids in the north-western Arabian Sea: implications of late Quaternary marine sedimentation and paleoclimate - Vikas Dev; Vishwesh Kumar Pathak; Rahul Dey; Madhurima Mazumder; Ajai Kumar Rai; Siddhartha Sankar Das (Arabian Journal of Geosciences, 2022)

Solar potential assessment over canal-top using geospatial techniques - Mudit Kapoor; Rahul Dev Garg (Arabian Journal of Geosciences, 2021)

Exploratory data analysis based efficient QRS-complex detection technique with minimal computational load - Jagdeep Rahul; Marpe Sora; Lakhan Dev Sharma (Physical and Engineering Sciences in Medicine, 2020)

Performance of graphene-added palm biodiesel in a diesel engine - Sumita Debbarma; Rahul Dev Misra; Biplab Das (Clean Technologies and Environmental Policy, 2020)

Performance study of modified basin-type single-slope solar distiller - Piyush Pal; Rahul Dev (Euro-Mediterranean Journal for Environmental Integration, 2018)

Using multi-source data and decision tree classification in mapping vegetation diversity - Gaurav Shukla; Rahul Dev Garg; Pradeep Kumar; Hari Shanker Srivastava; Pradeep Kumar Garg (Spatial Information Research, 2018)

Sugarcane ratoon discrimination using LANDSAT NDVI temporal data - Sandeep Kumar Singla; Rahul Dev Garg; Om Prakash Dubey (Spatial Information Research, 2018)

Cloud computing for energy requirement and solar potential assessment - Mudit Kapoor; Rahul Dev Garg (Spatial Information Research, 2018)

An effective implementation and assessment of a random forest classifier as a soil spatial predictive model - Gaurav Shukla; Rahul Dev Garg; Hari Shanker Srivastava; Pradeep Kumar Garg (International Journal of Remote Sensing, 2018)

Novel nanoformulation to mitigate co-effects of drugs of abuse and HIV-1 infection: towards the treatment of NeuroAIDS - Rahul Dev Jayant; Venkata S. R. Atluri; Sneham Tiwari; Sudheesh Pilakka-Kanthikeel; Ajeet Kaushik; Adriana Yndart; Madhavan Nair (Journal of NeuroVirology, 2017)

Estimation of Production Cost of Pure Plant Oils and Biodiesels from Karanja, Palm and Soapnut Plantations Through Financial Analysis - Jibanananda Jena; Rahul Dev Misra (Small-scale Forestry, 2014)

Influence of climate on incidences of malaria in the Thar Desert, northwest India - Deepak Jhajharia; Surajit Chattopadhyay; Rahul R. Choudhary; Vas Dev; Vijay P. Singh; Shankar Lal (International Journal of Climatology, 2013)
Climatic variability and rise in temperature are considered as the key determinants to the transmission of malaria. In the present study, the trends in the cases of malaria caused by Plasmodium falciparum and Plasmodium vivax were investigated by using the nonparametric Mann‐Kendall test after removing the effect of significant lag‐1 serial correlation from the time series of cases of malaria incidence by pre‐whitening in annual, seasonal, and monthly time scales at Bikaner, located in the Thar Desert of Rajasthan, in northwest India. Multi‐collinearity within the datasets under consideration was investigated by means of correlation matrix, the Bartlett sphericity test, and the Kaiser‐Meyer‐Olkin measure of sampling adequacy, subsequent to which it was removed by using principal component analysis. Finally, artificial neural network models were employed to predict cases of malaria incidence caused by P. falciparum and P. vivax at various scales. During the last 34 years from 1975 to 2008, P. falciparum malaria incidence cases have been found to increase significantly corresponding to monthly (April and September) and seasonal (monsoon) time scales over Bikaner. On the other hand, no significant trends were observed in P. vivax malaria cases at Bikaner. Concomitant increases in P. falciparum cases of malaria incidence and observed temperature increases at Bikaner hint that P. falciparum malaria may have grown significantly under the warming climate of the Thar Desert. Copyright © 2012 Royal Meteorological Society

Solubility-Modulated Asymmetric Membrane Tablets of Triprolidine Hydrochloride: Statistical Optimization and Evaluation - Rahul Dev; Anil Kumar; Kamla Pathak (AAPS PharmSciTech, 2012)